Survival of patients with mantle cell lymphoma in the rituximab era: Retrospective binational analysis between 2000 and 2020 - Harmanen Minna; Hujo Mika; Sund Reijo; Sorigue Marc; Khan Madiha; Prusila Roosa; Klaavuniemi Tuula; Kari Esa; Jantunen Esa; Sunela Kaisa; Rajamäki Aino; Alanne Erika; et al. (WILEY, 2025)
Mantle cell lymphoma (MCL) is a rare peripheral B-cell lymphoma characterised by eventual relapse and progression towards a more aggressive disease biology. With the introduction of rituximab- and cytarabine-based immunochemotherapy regimens, the prognosis of the disease has changed dramatically over the last two decades. To assess the real-world survival of patients with MCL, we used a population-based cohort of 564 patients with MCL who were diagnosed and treated between 2000 and 2020. Patient data were collected from seven Finnish treatment centres and one Spanish treatment centre. For the entire patient population, we report a 2-year overall survival (OS) rate of 77%, a 5-year OS of 58%, and a 10-year OS of 32%. The estimated median OS was 80 months after diagnosis. MCL is associated with increased mortality across the entire patient population. Additionally, we assessed the survival of patients after MCL relapse with the aim of establishing a cut-off point of prognostic significance. Based on our statistical analysis of survival after the first relapse, disease progression within 24 months of the initial diagnosis should be considered as a strong indicator of poor prognosis.